A simple method of computing the catch time - Clarke, Nancy E. (Ars mathematica contemporanea, 2014)
We describe a simple method for computing the maximum length of the game cop and robber, assuming optimal play for both sides.
Keywords: catch time; Cops and Robber; games involving graphs; pursuit game